Traduire sa nation. Identité et littérature canadienne-française au XIXe siècle - Colpron-Bergsma, Léonore (Université de Montréal, 2025)
Keywords: Anglophones; Francophones; Nationalisme; Traduction

Les dépatriés : histoire politique, culturelle, juridique et transatlantique des francités canadiennes (1763-1860) - Baraton, Édouard (Université du Québec à Montréal, 2024)
Keywords: Francophones; Français; Nationalisme

Enfant et esclave à Montréal: un angle mort de la recherche - Deslandres, Dominique (Revue d'histoire de la Nouvelle-France, 2024)
Keywords: Autochtones; Enfants; Esclaves

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

Le High School of Montreal: fer de lance de l'enseignement anglo-protestant - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Anglophones; High School of Montreal; Protestants

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

BRAININ, REUBEN - Orenstein, Eugene (Dictionnaire biographique du Canada, 2023)

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Éclairer et perfectionner l’esprit : l’éducation libérale et le délicat compromis entre raison et foi dans les écoles classiques de langue anglaise au Bas-Canada (1800-1840) - McCutcheon, Shawn (Études d'histoire religieuse, 2022)
Keywords: Langue; Libéralisme

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Montréal, haut lieu de la diplomatie autochtone - Arsenault, Mathieu (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Autochtones; Parlement

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

British Philanthropists and the Imperial Imagination or The Case of the Canadians Distressed by Fire at Montreal - Eamon, Michael (Canadian Historical Review, 2020)
Keywords: Britanniques; Incendies; Philanthropie

L’intimité française avec la " sauvagerie " à Montréal aux 17e-18e siècles - Deslandres, Dominique (Dix-huitième siècle, 2020)
Keywords: Autochtones; Criminalité; Délinquance; Français

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

GOLDSTEIN, MAXWELL - Lapidus, Steven (Dictionnaire biographique du Canada, 2020)

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Les hommes d'Église français dans la migration vers le Canada, 1842-1914 - Balloud, Simon (Université de La Rochelle et Université du Québec à Montréal, 2019)
Keywords: Communautés religieuses; Français

Histoire d’un système judiciaire à plusieurs vitesses: analyse intersectionnelle des procès pour meurtre dans la juridiction de Montréal entre 1700 et 1760 - Berthelet, Marie-Ève (Université de Montréal, 2019)
Keywords: Autochtones; Criminalité; Femmes

La mort du soldat William Hands. Violence urbaine, tensions politiques et justice criminelle à Montréal, 1835 - Harvey, Louis-George (Les Cahiers des Dix, 2019)
Keywords: Britanniques; Criminalité; Partis politiques

Les Québécois d'origine italienne. Une longue histoire - Linteau, Paul-André (Cap-aux-Diamants, 2019)
Keywords: Italiens

Familles montréalaises et élection de tutelle au temps du choléra: genre, appartenance ethnique et pratique judiciaire - Michaud-Guindon, Alexandre (Université du Québec à Montréal, 2019)
Keywords: Choléra; Droit; Famille; Mortalité; Veuvage; Épidémies

Les journalistes d'origine française au Québec au XIXe siècle - Roy, Fernande (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Canada (Le); Français; Journalistes; Patrie (La); Presse (La)

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman, William; Photographie

A Population Takes Flight: The Irish Famine Migration in Boston, Montreal, and Liverpool, and the Politics of Marginalization and Criminalization - Horner, Dan (The Criminalization of Migration: Context and Consequences, 2018)
Keywords: Irlandais

"Like a Thread of Gold". Tracing Alfred Perry's Lifelong Engagement with Montreal's Politics of Ethnic Confrontation - Horner, Dan (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Assurance; Gavazzi, Alessandro; Hôpital Douglas; Hôpitaux psychiatriques; Incendies; Parlement; Émeutes

Social Relations in Nineteenth-Century Montreal: Two Cultural Streams - Lamonde, Yvan (Montreal: The History of A North American City, 2018)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition

Montreal's Jews and the Public School System - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Juifs

Careful Coexistence: The Canadians and British in Montreal prior to 1800 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet, Fleury; Protestants; Écossais

Kin Keeping and Family Storytelling in Nineteenth-century French-Canadian Immigrant Letters: The Bergevin Corpus - Hurlburt, Sarah (Histoire sociale / Social History, 2017)
Keywords: Famille

Histoire des Juifs du Québec - Anctil, Pierre (Boréal, 2017)
Keywords: Juifs

Paysage linguistique et hybridité identitaire dans le roman en Belgique francophone et au Québec (1830-1913) - Bergeron-Proulx, Julie (Cahiers franco-canadiens de l'Ouest, 2017)
Keywords: Chauveau, Pierre-Joseph-Olivier; Gérin-Lajoie, Antoine; Lacombe, Patrice; Langue; Roman; Écrivains

Des noirs sous un voile blanc: métissage et abolition tranquille de l’esclavage - Mackey, Frank (Cap-aux-Diamants, 2017)
Keywords: Esclaves; Noirs

Des Écossais à Montréal, aux XVIIIe et XIXe siècles - Ouellet, Jeannine (Histoire Québec, 2017)
Keywords: Fourrure; Hommes d'affaires; Marchands; Écossais

The Montreal Emigrant Society - Coleman, Brian (Quebec Studies, 2016)
Keywords: Britanniques

La traite des pelletries aux XVIIe et XVIIIe siècles - Delâge, Denys (Les Cahiers des Dix, 2016)
Keywords: Autochtones; Britanniques; Fourrure; Français; Métis

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

Une émeute incendiaire: la destruction du parlement à Montréal (25 avril 1849) - Roussin, Éric (Histoire Québec, 2016)
Keywords: Anglophones; Francophones; Incendies; Parlement; Émeutes

La coexistence des communautés canadienne et britannique vue par le Montreal Herald (1837-1839) - Deschamps, François (Cap-aux-Diamants, 2015)
Keywords: Britanniques; Montreal Herald

Procès et conflits linguistiques à Montréal au début du XIXe siècle - Garneau, Jean-Philippe (Cap-aux-Diamants, 2015)
Keywords: Anglophones; Britanniques; Langue

Les Anglais de Montréal - Leitch, Gillian (Montréal en tête, 2015)
Keywords: Britanniques

Les écrits urbains sous contrôle. L'exemple de Montréal - Artières, Philippe (Essais, 2014)
Keywords: Enseignes; Français; Publicité

La communauté écossaise de Montréal. Histoire et questions identitaires - Bourbeau, Catherine (Histoires d'immigrations à Montréal, 2014)
Keywords: Écossais

Se construire et s'affirmer par les lieux. Un regard sur les présences autochtones à Montréal - Comat, Ioana (Université Laval, 2014)
Keywords: Autochtones; Centre d'amitié autochtone

L'Institut canadien de Montréal et l'intelligentsia protestante: réactions, relations et perceptions - Cousson, Claire (Huguenots et protestants francophones au Québec, 2014)
Keywords: Francophones; Institut canadien; Protestants

Antisémitisme et collèges, 1825-1910 - Debien, Léon (Bulletin d'histoire politique, 2014)
Keywords: Collèges classiques; Juifs

Shame upon you as men!: Competing Visions of Masculine Authority in the Aftermath of Montreal's Gavazzi Riot - Horner, Dan (Gender History: Canadian Perspectives, 2014)
Keywords: Britanniques; Canadiens français; Gavazzi, Alessandro; Irlandais; Émeutes

Les Écossais de Montréal - Leitch, Gillian (Montréal en tête, 2014)
Keywords: Écossais

Entre les tensions et les groupes de pression: les Britanniques de Montréal au temps des rébellions - Leitch, Gillian I. (De la représentation à la manifestation. Groupes de pression et enjeux politiques au Québec, XIXe et XXe siècles, 2014)
Keywords: Britanniques; Rébellions

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

L'incendie du parlement à Montréal en 1849: un événement occulté: présentation - Comeau, Robert; Deschênes, Gaston (Bulletin d'histoire politique, 2013)
Keywords: Britanniques; Incendies; Parlement

Le filibuster sur la Loi d'indemnisation (1849) - Deschênes, Gaston (Bulletin d'histoire politique, 2013)
Keywords: Britanniques; Rébellions

L'hostilité entre Irlandais catholiques et Irlandais protestants. La Saint-Barthélemy de Montréal (1853) - Germain, Jean-Claude (Montréal en tête, 2013)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

Les Irlandais à Montréal. Une présence marquante dès le XIXe siècle - Jolivet, Simon (Montréal en tête, 2013)
Keywords: Irlandais; Saint-Patrick (paroisse)

L'esclavage et les Noirs à Montréal, 1760-1840 - Mackey, Frank (Hurtubise, 2013)
Keywords: Esclaves; Noirs

Silver and Hotcakes and Beer: Irish Montreal in the 1840s - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 2013)
Keywords: Auberges; Irlandais

St. Patrick's and the Irish Catholics - Olson, Sherry (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Embodying Nation: Indigenous Sports in Victorian Montreal, 1860-1885 - Poulter, Gillian (Contesting Bodies and Nation in Canadian History, 2013)
Keywords: Autochtones; Nationalisme

Le déclin d'une élite: francophones d'Anvers - anglophones de Montréal - Préaux, Céline (P.I.E. Peter Lang, 2013)
Keywords: Anglophones

La Société Saint-Jean-Baptiste de Montréal - Racine, Denis (Cap-aux-Diamants, 2013)
Keywords: Duvernay, Ludger; Société Saint-Jean-Baptiste

Des souvenirs pour l’avenir - Brabander, Richard (Cap-aux-Diamants, 2012)
Keywords: Allemands

Le financement des écoles publiques à Montréal et à Toronto (1841-1997): un baromètre pour mesurer les rapports entre la majorité et la minorité - Croteau, Jean-Philippe (Revue de l'histoire de l'éducation / Historical Studies in Education, 2012)
Keywords: Anglophones; Francophones; Protestants

Des femmes anglo-protestantes s'attaquent aux questions sanitaires. Les multiples facettes des soins de santé à Montréal, au XIXe siècle et au début du XXe siècle - Harvey, Janice (L'incontournable caste des femmes. Histoires des services de santé au Québec et au Canada, 2012)
Keywords: Anglophones; Bénévolat; Femmes; Montreal Local Council of Women; Protestants

La sociabilité montréalaise au XIXe siècle: la présence des cultures francophone et anglophone - Lamonde, Yvan (Histoire de Montréal et de sa région, 2012)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition

La mosaïque historique germano-québécoise - Meune, Manuel (Cap-aux-Diamants, 2012)
Keywords: Allemands

Cohabiter avec et contre l'autre: Canadiens et Britanniques à Montréal avant 1800 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet, Fleury; Protestants; Écossais

Dans le Montréal de Papineau. L'aventure de Serafino Giraldi - Aubin, Georges (Montréal en tête, 2011)
Keywords: Hôtellerie; Italiens; Papineau (famille); Papineau, Louis-Joseph

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Le déclin d'une élite: l'évolution du discours communautaire public des francophones d'Anvers et des anglophones de Montréal - Préaux, Céline (Université Libre de Bruxelles, 2011)
Keywords: Anglophones

Les communautés juives de Montréal. Histoire et enjeux contemporains - Anctil, Pierre; Robinson, Ira (Septentrion, 2010)
Keywords: Juifs

Évolution du cheptel équin et de la culture équestre dans la vallée du Saint-Laurent sous l'influence britannique, 1760-1850 - Bélanger, Andrée (Université Laval, 2010)
Keywords: Britanniques; Chevaux

Quebec: Montreal - Henry, Natasha L. (Emancipation Day: Celebrating Freedom in Canada, 2010)
Keywords: Esclaves; Noirs

Les missions amérindiennes près de Ville-Marie - Loiselle, François (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Keywords: Autochtones; Communautés religieuses; Jésuites; Missions; Sulpiciens

Done With Slavery: The Black Fact in Montreal, 1760-1840 - Mackey, Frank (McGill-Queen's University Press, 2010)
Keywords: Esclaves; Noirs

Brève introduction à l'histoire juive - Robinson, Ira (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs

Le judaïsme à Montréal - Robinson, Ira (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs

Le combat du Montreal Herald, organe du Doric Club - Deschamps, François (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Clubs; Francs-Maçons; Loyalistes; Montreal Herald; Rébellions

Fabled city: the Jews of Montreal - King, Joe (Price-Patterson, 2009)
Keywords: Juifs

Oka, 20 ans déjà! Les origines lointaines et contemporaines de la crise - Lepage, Pierre (Recherches amérindiennes au Québec, 2009)
Keywords: Autochtones

Ludger Duvernay, le journal La Minerve et la construction identitaire canadienne - Monière, Denis (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Journalistes; Minerve (La); Rébellions; Société Saint-Jean-Baptiste

Becoming Native in a Foreign Land: Sport, Visual Culture and Identity in Montreal, 1840-85 - Poulter, Gillian (University of British Columbia Press, 2009)
Keywords: Autochtones; Britanniques; Français

Le légalisme à la sulpicienne - Savard, Rémi (Recherches amérindiennes au Québec, 2009)
Keywords: Autochtones; Communautés religieuses; Sulpiciens

Le jeu de la crosse à Montréal au XIXe siècle - Ferland, Daniel (Patrimoine, 2008)
Keywords: Autochtones; Crosse

Quatre siècles d’immigration française au Canada et au Québec - Linteau, Paul-André (France-Canada-Québec. 400 ans de relations d’exception, 2008)
Keywords: Français

Canada’s Jews: A People’s Journey - Tulchinsky, Gerald (University of Toronto Press, 2008)
Keywords: Juifs

Un titre honorifique ambigu de Jacques Viger: "Premier président de la Société Saint-Jean-Baptiste de Montréal" - Beaudoin, Léo (Montréal en tête, 2007)
Keywords: Clubs; Duvernay, Ludger; Société Saint-Jean-Baptiste; Viger, Jacques

Les rapports entre Autochtones et Blancs dans le sport de la crosse de la région de Montréal au XIXe siècle - Ferland, Daniel (Université de Sherbrooke, 2007)
Keywords: Autochtones; Crosse

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

Saint-Patrick et les paroissiens irlandais - Olson, Sherry (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Les Iroquois et les terres du Sault Saint-Louis: étude d'une revendication territoriale (1760-1850) - Pepin, Karol (Université du Québec à Montréal, 2007)
Keywords: Autochtones; Communautés religieuses; Iroquois; Jésuites

Trois leaders irlandais au Bas-Canada - Rompré, Mathieu (Cap-aux-Diamants, 2007)
Keywords: Irlandais; O'Callaghan, Edmund B.; Tracey, Daniel; Waller, Jocelyn

The Curious Tale of the Scots and the Fur Trade: An Historiographical Account - Bumsted, J. M. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Fourrure; Écossais

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

Joseph Marcoux et les Iroquois du Sault-Saint-Louis (1819-1855) - Herpin, Alexandra (Université d'Angers, 2006)
Keywords: Autochtones; Iroquois

Baron Byng to bagels: tales of Jewish Montreal - King, Joe (Montreal Jewish Publication Society, 2006)
Keywords: Juifs

A Man's a Man because of That: The Scots in the Canadian Military Experience - Klepak, H. P. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Armée; Écossais

Scottish Identity and British Loyalty in Early-Nineteenth-Century Montreal - Leitch, Gillian I. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Saint Andrew's Society; Écossais

The Importance of Being English? Identity and Social Organisation in British Montreal, 1800-1850 - Leitch, Gillian I. (Université de Montréal, 2006)
Keywords: Britanniques

"In the Hallowed Name of Religion": Scots and Public Education in Nineteenth-Century Montreal - MacLeod, Roderick (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Écossais

Sojourners in the Snow? The Scots in Business in Nineteenth-Century Canada - McCalla, Douglas (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Marchands; Écossais

Butcher, Baker, Cabinetmaker? A View of Montreal's Scottish Immigrant Community from 1835 to 1865 - McNabb, Heather (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Écossais

Une histoire sociale du curling au Québec, de 1807 à 1980 - Richard, Pierre (Université du Québec à Trois-Rivières, 2006)
Keywords: Clubs; Curling; Femmes; Francophones; Montreal Curling Club

A Kingdom of the Mind: How the Scots Helped Make Canada - Rider, Peter E.; McNabb, Heather (McGill-Queen's University Press, 2006)
Keywords: Écossais

"Bonnie Lassies" and a "Coat of Many Colours": Highland-Inspired Clothing at the McCord Museum - Stack, Eileen (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Musée McCord; Musées; Vêtements; Écossais

Sir William Logan and Sir J.W. Dawson: Victorian Geology as Scottish Science in a New World Environment - Zeller, Suzanne (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Dawson, William; Géologie; Logan, William Edmond; Écossais

A Rooted Horror: Thomas D'Arcy McGee and Secret Societies, 1845-68 - A. Wilson, David (The Canadian Journal of Irish Studies, 2005)
Keywords: Féniens; Irlandais; McGee, Thomas D'Arcy; Nationalisme

The Radicalization of the Montreal Irish: The Role of the "Vindicator" - Jackson, James (The Canadian Journal of Irish Studies, 2005)
Keywords: Irlandais; Rébellions; The Vindicator

Le théâtre francophone à Montréal de 1855 à 1880: les causes d'un développement tardif - Laflamme, Jean (Maxime, 2005)
Keywords: Francophones; Théâtre

The Scots in Montreal and Their Quest to Stay Scottish - Leitch, Gillian I. (Montreal-Glasgow, 2005)
Keywords: Écossais

The Scots of Montreal: a pictorial album - Marrelli, Nancy; Dardick, Simon (Véhicule Press, Musée McCord et St. Andrew's Society of Montreal, 2005)
Keywords: Écossais

Irish Politics on Parade: The Clergy, National Societies, and St. Patrick's Day Processions in Nineteenth-century Montreal and Toronto - Trigger, Rosalyn (Histoire sociale / Social History, 2004)
Keywords: Irlandais; Processions

La culture littéraire de langue anglaise au Bas-Canada - Gerson, Carole (Histoire du livre et de l'imprimé au Canada, vol. I (des débuts à 1840), 2004)
Keywords: Anglophones; Francophones

Black then: Blacks and Montreal, 1780-1880's - Mackey, Frank (McGill-Queen's University Press, 2004)
Keywords: Noirs

Ethnic Partition of the Work Force in 1840s Montréal - Olson, Sherry (Labour / Le travail, 2004)
Keywords: Anglophones; Britanniques; Français; Irlandais; Protestants; Travail

'Very Picturesque and Very Canadian': The Blanket Coat and Anglo-Canadian Identity in the Second Half of the Nineteenth Century - Stack, Eileen (Fashion. A Canadian Perspective, 2004)
Keywords: Anglophones; Vêtements

Print and Black Canadian Culture - Williams, Dorothy (History of the Book in Canada, vol. II (1840-1918), 2004)
Keywords: Journalistes; Noirs; Écrivains

Irish-Catholic Leadership in Nineteenth Century Montreal - Leitch, Gillian (Cahiers d'histoire, 2003)
Keywords: Irlandais

Les Iroquois de Kahnawake et de Kanesatake et les Rébellions de 1837-1838 - Sossoyan, Matthieu (Bulletin d'histoire politique, 2003)
Keywords: Autochtones; Iroquois; Rébellions

The Challenge of the Irish Catholic Community in Nineteenth-Century Montreal - Olson, Sherry; Thornton, Patricia (Histoire sociale / Social History, 2002)
Keywords: Irlandais

La justice coloniale britannique et les Amérindiens au Québec 1760-1820: I - En terres amérindiennes - Delâge, Denys; Gilbert, Étienne (Recherches amérindiennes au Québec, 2002)
Keywords: Autochtones; Britanniques

Les Juifs de Montréal : trois siècles de parcours exceptionnels - King, Joe (Carte blanche, 2002)
Keywords: Juifs

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith, Donald

Black Media in Montreal: In Defense of Abyssinia - Williams, Dorothy (Proceedings of the Seventh Annual History in the Making Conference: History and Media, Concordia University, March 2001, 2002)
Keywords: Esclaves; Journalistes; Noirs

From the Ghetto to the Main: the Story of the Jews of Montreal - King, Joe (Montreal Jewish Publications Society, 2001)
Keywords: Juifs

La Vita e bella - Létourneau, Isabelle (Continuité, 2001)
Keywords: Petite-Italie (quartier); Quartiers

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Le théâtre francophone à Montréal de 1855 à 1880: une institution qui tarde - Laflamme, Jean (Université de Montréal, 2000)
Keywords: Francophones; Théâtre

Les Canadiens français, l'histoire et la démocratie: l'interprétation de Pierre Elliott Trudeau - Ouellette, Mélanie (Mens, 2000)
Keywords: Trudeau, Pierre Elliott